Analyzing System Security Architecture in Concept Phase Using UAF Domains. Issue 2 (5th July 2022) - López García, Juan José; Pereira, Daniel Patrick
ABSTRACT: This paper presents combining MBSE (Model‐Based System Engineering) and STPA (Systems‐Theoretic Process Analysis) to mitigate security risks at an early stage of system development and to increase agility when developing or modifying architectures. The MBSE approach states that the systems development process should have a system model or a set of models as the unique source of truth. From the system model or a set of models, systems engineers of different specialties should be able to extract the information needed to perform their job. However, some specialties usually create their artefact apart from the model to perform the analysis, breaking the premises of MBSE to have a unique source of truth leading to out‐of‐date artefacts. This article proposes extending the Unified Architecture Framework (UAF) Profile (UAFP) to enable safety and security systems engineers to perform their analysis from the early stage of a system development process.